The Jurist and the Theologian Speculative Theology in Shāfiʿī Legal Theory - Eissa, Mohamed Abdelrahman (Gorgias Press, 2017)
This in-depth study examines the relation between legal theory (uṣūl al-fiqh) and speculative theology (ʿīlm al-kalām). It compares the legal theory of four classical jurists who belonged to the same school of law, the Shāfiʿī school, yet followed three different theological traditions. The aim of this comparison is to understand to what extent, and in what way, the theology of each jurist shaped his choices in legal theory